Forensic technology: concepts, objectives and principles - V. M. Kyselov (Bulletin of Kharkiv National University of Internal Affairs)
It is established that forensic technology is a branch of forensic science which uses a variety of methods, instruments and technical means to collect, examine and interpret physical evidence at a crime scene in order to detect, investigate and document crimes and their perpetrators. Forensic technology is based on scientific principles and technologies and includes many different methods, such as ballistics, fingerprinting, DNA analysis, document examination, photography, video recording, etc.